If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-11=-4(-7-5x)+7(x+6)
We simplify the equation to the form, which is simple to understand
-11=-4(-7-5x)+7(x+6)
Reorder the terms in parentheses
-11=+(+28+20x)+7*(x+6)
Remove unnecessary parentheses
-11=+28+20x+7+*(+x+6+)
Reorder the terms in parentheses
-11=+28+20x+(+7x+42)
Remove unnecessary parentheses
-11=+28+20x+7x+42
We move all terms containing x to the left and all other terms to the right.
-20x-7x=+28+42+11
We simplify left and right side of the equation.
-27x=+81
We divide both sides of the equation by -27 to get x.
x=-3
| 7*x=42 | | 2(-x+4)-5(-2-x)=4+5(3*2-2*2) | | 36+2x=72 | | -(-8y+2)-(-7y-7)=3 | | (M-6)=4 | | x+0.2x+0.06x=50.40 | | 15+6x=51 | | (-1,-1),(1,-3),(2,0)= | | 6x+14=9x-1 | | 119=-6+5(-3x+4) | | 5(x+1)+30=-2x | | 4-1.75= | | x/5(x+10y-4) | | 5=-4+2x | | -9=-3v-6v | | 4(m+9)=-3(m-4) | | (7,-2)(-6,-1)= | | 43+5x=48 | | -7-6a=-31 | | X-3=5x-4 | | X+3=56 | | 20+2x=50 | | 3(2x-3)=4 | | 6x^2-27x-20=0 | | (6,7-3)(-8,-11)= | | f(x)=x^2-6x+11 | | (-3,5),(-3,-3),(3,-3)= | | 2+30/t=4 | | (3x-2)(4x+9)=0 | | 7x/5+4x/5 | | (4x-9y)(3x+11y)=0 | | x+x+x+5+x+7=40 |